Legally Speaking Legal Challenges to Generative AI, Part II: Deliberating on inconclusive AI-generated policy questions. - Samuelson, Pamela (Communications of the ACM, 2023)
This article presents the accompanying piece to the author’s first installment on legal challenges surrounding generative artificial intelligence (AI) in the July issue of Communications of the ACM. This article focuses on two lawsuits brought on for illegal use of images and captions for AI training data, where Stability AI Ltd. is the defendant in both. The author presents a look at previous copyright infringement cases and how the outcome of those might inform these current cases.